Evaluating pathogenicity of rare variants from dilated cardiomyopathy in the exome era - Norton, Nadine (2012)
BACKGROUND: Human exome sequencing is a recently developed tool to aid in the discovery of novel coding variants. Now broadly applied, exome sequencing datasets provide a novel opportunity to evaluate the allele frequencies of previously published pathogenic rare variants. METHODS AND RESULTS: We examined the exome dataset from the NHLBI Exome Sequencing Project (ESP) and compared this dataset with a catalog of 197 previously published rare variants reported as causative of dilated cardiomyopathy (DCM) from familial and sporadic cases. Of these 197, 33 (16.8%) were also present in the ESP database, raising the question of whether they were uncommon polymorphisms. Supporting functional data has been published for 14 of the 33 (42%), suggesting they are unlikely to be false positives. The frequencies of these functional variants in the ESP dataset ranged from 0.02–1.33% (median 0.04%), which when applied as a cut-off to filter variants in a DCM pedigree identified an additional DCM candidate gene. A greater proportion of sporadic DCM cases had variants that were present in the ESP dataset vs novel variants (i.e. not in ESP; 44% vs 21%), p=0.002), suggesting some of the variants identified as disease causing in sporadic DCM are either false positives or low penetrance alleles in human populations. CONCLUSIONS: Rare nonsynonymous variants identified in DCM subjects also present at very low frequencies in public databases are likely relevant for DCM. Allele frequencies >0.04% are of less certain pathogenicity, especially if indentified in sporadic cases, although this cut-off should be viewed as preliminary.